Enfermedades bucodentales y factores de riesgo en niños con dentición decidua. Revisión bibliográfica - Abad Castillo, Arelis del Cisne (2023)
Oral diseases are a universal public health problem with vast health and economic burdens, presenting a complex etiology and interrelated with risk factors that trigger it. This bibliographic research aimed to identify oral diseases in children with deciduous dentition. Along with the risk factors that influence their development. Similarly, establish a proposal of preventive measures for each oral disease identified. Methodology: an analytical, descriptive, and retrospective study developed through the collection of bibliographic information, taking into account the criteria of both inclusion and exclusion, where the universe was composed of 109 articles, of which 62 were the sample. The results obtained in the study showed that early childhood caries, traumatic dental injury, and gingivitis are the three most prevalent diseases in the child population; Regarding the risk factors related to pathologies, we have: for caries dietary habits, socio-demographic factors, and oral hygiene habits; in oral trauma conditions such as increased Overjet (>3-5 mm) and inadequate lip covering; and for gingivitis the accumulation of dental biofilm (bacterial plaque). Finally, we proposed a proposal for preventive measures for each disease based on the literature reviewed.